The effect of price framing and customer experience in purchase decision: field experiment with a jewelry store - Jhun, Janete Hee Youn (2018)
Price promotions are a ubiquitous practice in the retail market and often consumers are overwhelmed by the variety of price schemes. Using a natural field experiment with a jewelry store, the present study tested the price framing effect and customer experience in purchase decision. The price framing effect was tested using three similar products offered alongside one another: 1 control with the regular price, 2 treatments designed to provide a positive transaction utility and price-quality perception - their prices were initially raised and then proportional discounts (10% and 20%) were applied, so that the final prices of all products amounted to be the same. The effect of customer experience was observed measuring the sales of two customers groups with different experience levels: retail customers (less experienced consumers) and wholesale customers (more experienced since they work as resellers). However, the hypotheses of the study were not confirmed, since the products treated with the price framing effect presented regression coefficients with low statistical significance, for both retail and wholesale customers. Considering that the experiment manipulated both price and discount, current literature on the subject indicates that the effects of quality perception that both present ended up conjoint and led to a null result. Some possible avenues to isolate these effects, as well as other lessons learned in the experiment, are discussed for future research.